A review of experimental mobile learning research in 2010–2016 based on the activity theory framework. (February 2019) - Chung, Ching-Jung; Hwang, Gwo-Jen; Lai, Chiu-Lin
Abstract: In this study, we systematically reviewed the experimental mobile learning studies published in 2010–2016. Moreover, the activity theory framework was adopted to investigate the insights and trends of mobile learning. That is, the dimensions of context, tools, control, communication, subjects and objectives were employed to analyze the studies. It was found that most experimental mobile learning studies engaged students in real-world contexts, and the activities were conducted based on the existing school curriculums. This means that researchers and school teachers noted the value of situating students in meaningful learning by helping them link what they had learned from the textbooks to real-world scenarios or daily life environments. In the meantime, the studies frequently involved the students in actively using mobile systems with communication facilities to acquire knowledge via interacting with peers, events, and specified real-world learning targets in the environment. On one hand, many researchers proposed to raise students' motivation; on the other hand, they expected to observe more of what the learners, particularly novices and low-achievement students, had done when observing their past interactions. Even so, it was found that mobile devices were considered a main way of allowing students to acquire self-learning materials rather than only mediation learning across contexts. As the current studies can be considered to contain blended rather than purely self-paced learning, there is still a large space for mobile learning progress and development. Highlights: A review on experimental m-learning was done based on the activity theory framework. The studies published in 2010–2016 were investigated to find the trends of m-learning. The context, tool, control, communication, subject and objective aspects were analyzed. The phenomena of the m-learning activities conducted in the studies were reported. Possible research issues of m-learning in the future were proposed.